Dual Relationships in Counselling: A Survey of British Columbian Counsellors - Nigro, Tracey; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 2007)
The British Columbian Members of the Canadian Counselling Association were surveyed, in order to explore their attitudes and experiences regarding dual relationships. Of 529 deliverable surveys, 206 usable returns yielded a response rate of 39%. The survey instrument collected data regarding respondents' characteristics and ethicality ratings of 39 dual relationship activity items. A number of significant relationships were found between respondents' characteristics and their ethicality ratings of the 39 dual relationship activity items. Nine matched-pairs of dual relationship activity items were analyzed for significant differences in counsellor's ratings. The results were compared with previously conducted research, and the implications of the results were discussed in regards to future practice and research.